1990
DOI: 10.1128/jcm.28.2.344-349.1990
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous anergic sera or purified protein derivative treatment induces modification in lymphocyte transformation of cells from patients with tuberculosis

Abstract: Peripheral blood mononuclear cells from 20 purified protein derivative (PPD)-reactive (PPD+) tuberculous patients were cultured in autologous, tuberculous anergic, or normal serum. After 12 h of incubation, the serum was eliminated and lymphocyte transformation with PPD was performed. Transformation was inhibited only in cells incubated with anergic serum. In contrast, cells from 11 anergic tuberculous (PPD-) individuals recovered the ability to respond to an optimal PPD dose after treatment with high PPD conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Analysis of T‐lymphocyte cytokine response is important in studying the immune response to mycobacterial tuberculosis and clinical course of the disease. In agreement with previously published studies, our results showed that the tuberculin‐negative patients with active pulmonary tuberculosis were mainly those with more serious forms of the disease in whom a prolonged duration of the disease should be anticipated [14, 26, 27]. A growing body of evidence suggest that the human immune response to infection is similarly mediated by T‐cell subpopulations secreting specific cytokine patterns.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of T‐lymphocyte cytokine response is important in studying the immune response to mycobacterial tuberculosis and clinical course of the disease. In agreement with previously published studies, our results showed that the tuberculin‐negative patients with active pulmonary tuberculosis were mainly those with more serious forms of the disease in whom a prolonged duration of the disease should be anticipated [14, 26, 27]. A growing body of evidence suggest that the human immune response to infection is similarly mediated by T‐cell subpopulations secreting specific cytokine patterns.…”
Section: Discussionsupporting
confidence: 90%